1971
DOI: 10.2466/pms.1971.33.3f.1163
|View full text |Cite
|
Sign up to set email alerts
|

Relations among Chronicity, Diagnosis, Premorbid Adjustment, Defensiveness and Two Measures of Perceptual Scanning

Abstract: Si~mmary.-The attention style of perceptual scanning has been related to the variables of chronicity, diagnosis, and premorbid adjustment. In addition, a functional defensive significance has been attributed to scanning. However, recent research has questioned the adequacy of the standard size-estimation task employed as a scanning measure. The current smdy explored relations among chronicity, diagnosis, premorbid adjustment, impulsivity and defensiveness, using eye movements and performance on a task with cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Eysenck, Granger, and Brengelmann (1957), in a relatively uncontrolled perimetric study, reported significantly reduced peripheral vision among neurotic and psychotic as compared to normal subjects. Haley (1971) and Scherer (1972) found that chronic schizophrenics had longer reaction times to visual stimuli presented in the periphery than normal subjects. Neale (1971) found that schizophrenics were unable to recognize letters presented in the near periphery (2-3 degrees) than normals.…”
Section: Visual-spatial Extensitymentioning
confidence: 99%
“…Eysenck, Granger, and Brengelmann (1957), in a relatively uncontrolled perimetric study, reported significantly reduced peripheral vision among neurotic and psychotic as compared to normal subjects. Haley (1971) and Scherer (1972) found that chronic schizophrenics had longer reaction times to visual stimuli presented in the periphery than normal subjects. Neale (1971) found that schizophrenics were unable to recognize letters presented in the near periphery (2-3 degrees) than normals.…”
Section: Visual-spatial Extensitymentioning
confidence: 99%
“…more hypervigilant and attuned to visual and auditory stimuli than were nonparanoids and other psychiatric groups (Haley, 1971;Lynn, 1963;Silverman, 1964aSilverman, , 1964bSilverman, , 1964c. Research dealing with the perceptual style (field dependence) concomitants of paranoia may also be relevant.…”
mentioning
confidence: 98%